Observation of 1H-1H J-couplings in fast magic-angle-spinning solid-state NMR spectroscopy - Daria Torodii; Jacob B. Holmes; Kristof Grohe; Rodrigo de Oliveira-Silva; Sebastian Wegner; Dimitrios Sakellariou; Lyndon Emsley (Nature Communications)
Abstract While 1H-1H J-couplings are the cornerstone of all spectral assignment methods in solution-state NMR, they are yet to be observed in solids. Here we observe 1H-1H J-couplings in plastic crystals of (1S)-(−)-camphor in solid-state NMR at magic angle spinning (MAS) rates of 100 kHz and above. This is enabled in this special case because the intrinsic coherence lifetimes at fast MAS rates become longer than the inverse of the 1H-1H J couplings. For example, at 160 kHz MAS the coherence lifetimes are longer than 20 ms, corresponding to refocused linewidths of less than 15 Hz. As a result, we are able to record two-dimensional 1H-1H J resolved spectra that allow the observation and measurement of 1H-1H J-couplings in solid camphor. The J-couplings also lead to unambiguous through-bond correlations in 1H-1H refocused incredible natural abundance double quantum transfer (INADEQUATE) and uniform-sign cross-peak double-quantum-filtered correlation spectroscopy (UC2QFCOSY) experiments.